Cesarean delivery in Nigeria: prevalence and associated factors―a population-based cross-sectional study - Asa Auta; Emmanuel O Adewuyi; Vishnu Khanal; Samson J Tapshak; Yun Zhao (BMJ Open)
Objective To investigate the prevalence and factors associated with caesarean delivery in Nigeria.Design This is a secondary analysis of the nationally representative 2013 Nigeria Demographic and Health Survey (NDHS) data. We carried out frequency tabulation, χ2 test, simple logistic regression and multivariable binary logistic regression analyses to achieve the study objective.Setting Nigeria.Participants A total of 31 171 most recent live deliveries for women aged 15–49 years (mother–child pair) in the 5 years preceding the 2013 NDHS was included in this study.Outcome measure Caesarean mode of delivery.Results The prevalence of caesarean section (CS) was 2.1% (95% CI 1.8 to 2.3) in Nigeria. At the region level, the South-West had the highest prevalence of 4.7%. Factors associated with increased odds of CS were urban residence (adjusted OR (AOR): 1.51, 95% CI 1.15 to 1.97), maternal age ≥35 years (AOR: 2.12, 95% CI 1.08 to 4.11), large birth size (AOR: 1.39, 95% CI 1.10 to 1.74) and multiple births (AOR: 4.96, 95% CI 2.84 to 8.62). Greater odds of CS were equally associated with maternal obesity (AOR: 3.16, 95% CI 2.30 to 4.32), Christianity (AOR: 2.06, 95% CI 1.58 to 2.68), birth order of one (AOR: 3.86, 95% CI 2.66 to 5.56), husband’s secondary/higher education level (AOR: 2.07, 95% CI 1.29 to 3.33), health insurance coverage (AOR: 2.01, 95% CI 1.37 to 2.95) and ≥4 antenatal visits (AOR: 2.84, 95% CI 1.56 to 5.17).Conclusions The prevalence of CS was low, indicating unmet needs in the use of caesarean delivery in Nigeria. Rural–urban, regional and socioeconomic differences were observed, suggesting inequitable access to the obstetric surgery. Intervention efforts need to prioritise women living in rural areas, the North-East and the North-West regions, as well as women of the Islamic faith.